Housing Dynamics, Empirical Facts and the Business Cycle - Zi-Yi Guo (Global Conference on Business and Finance Proceedings, 2017)
The recent financial crisis has witnessed the importance of the housing markets in macroeconomic fluctuations. We investigate the correlation between housing dynamics and the business cycle for a variety of countries. Our empirical results confirm the two daunting facts faced by lots of macroeconomic modelers: (i) house prices are highly volatile and closely correlated with the business cycle, which is at odds with the evidence that rental prices are relatively stable and almost uncorrelated with the business cycle; and (ii) residential investment leads the business cycle while nonresidential investment moves contemporaneously with the business cycle.
Keywords: 330